When yoer child has an eating disorder : Astep - by - step workbook for farents and other coregivers - Natenshon Abigai H. (Jossey-Bass, 1999)
Bài tập hướng dẫn giáo dục trẻ em và các chế độ ăn uống dinh dưỡng.